A study about the economic activities of Orang Seletar in Johor Bahru: addressing challenges in fishing practises through architectural solutions - Mohd Salleh, Muhammad Zahiruddin; Mohd For, Liyana Mahfuzah; Samadi, Zalina; Mohd Shahrain, Siti Hajar; Mustapha Kamal, Fatmah Adhilah (UiTM Press, 2025)
This research investigates the economic activities of the Orang Seletar, also known as Orang Laut, an indigenous community in Johor Bahru, Malaysia, focusing on their fishing practises and proposing architectural interventions to address the challenges faced by Seletar fishermen in the fishing ecosystem. As urbanisation and industrialisation reshape their environment, the Orang Seletar face increasing challenges in sustaining their traditional livelihoods. Despite the centrality of fishing to their economy, limited research addresses the spatial and architectural needs required to support these practises. The research objectives are to explore their fishing routines, understand the fishing ecosystem, and propose architectural solutions to address the challenges they face. Using a qualitative approach, the research involves document analysis, observations, and interviews with Seletar fishermen. Research findings include a comprehensive Orang Seletar sociocultural context, a detailed understanding of their linear fishing ecosystem, the identification of key challenges such as inadequate facilities or disrupted access to resources, and the development of architectural solutions that align with their cultural and economic needs based on the benchmarks from global indigenous community strategy. This research is significant for bridging the gap between indigenous economic practises and architectural design, offering insights and practical recommendations for cultural sensitivity and sustainable spatial interventions that can improve the livelihoods of the Orang Seletar.